FINANCIAL PLANNING MODEL FOR ESTABLISHING A NEW BUSINESS A CASE STUDY ON “BLUE OCEAN” RESTAURANT - Salamin, Petrus Pius; Hermawan, Francisca (Universitas Muhammadiyah Yogyakarta, 2019)
This article aims to (1) design an appropriate financial planning model for a restaurant, (2) give an example of a financial planning model that may be can be applied to the same kind of business, (3) give a guidance to the owner and employee in daily financial operational activity. This article is based on (1) the analysis of theory and its application in a real business, especially at Blue Oceanrestaurant, as a new business, (2) survey on the surrounded area, and (3) interview with the business’ owners in the surrounding area .We have analyzed all the data and information, and then try to describe it in a financial planning model, consisting of needs and uses of investment funds (Start-up cost), start-up balance sheet, pro forma income statement, cash budget, pro forma endingbalance sheet.It can be concluded that a financial planning model will give a clear guidance to the owner and the employeehow to manage daily operation and financial control, and it is clear what financial goals and objectives have to be achieved by the owner (in the next five years).